Developing digital applications for tailored communication in orthopaedics using a Research through Design approach. (January 2019) - Groeneveld, Bob; Melles, Marijke; Vehmeijer, Stephan; Mathijssen, Nina; Dekkers, Tessa; Goossens, Richard
Objective: Tailored communication and information provision is expected to contribute to patient-centred care (PCC) in total hip arthroplasty (THA). In previous research, three subgroups of THA patients were identified that are similar in their clinical, psychological and communication characteristics. Preliminary subgroup-specific design guidelines were also formulated. Using these insights as a starting point, a theoretical framework was developed for tailored information provision and communication using digital applications. This study aims to refine the framework as well as subgroup-specific design guidelines for digital applications. Methods: This study uses a Research through Design (RtD) approach, generating insights both from the development and evaluation of prototypes in the early design stage. Paper-based prototypes will be made for each subgroup and evaluated with patients and care providers. Semi-structured interviews are held with participants exploring their experiences with the prototype. A quasi-experiment with a non-random control cohort is used to validate the qualitative findings. Post-surgery consultations with and without prototype are videotaped and scored using a structured instrument. Results: A design diary will be used to summarize design decisions and considerations. Feedback from participants is analysed inductively. Adaptations in subgroup-specific guidelines will be based on comparison of verbal feedback and descriptive statistics from consultations with and without prototype. Conclusions: Although mixed-method feasibility studies of digital health interventions are common, this protocol also considers the utility of the early design process and the designer's perspective for realizing PCC and tailored care.